The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The 5th International Conference on Automation, Robotics and Applications 2011
DOI: 10.1109/icara.2011.6144890
|View full text |Cite
|
Sign up to set email alerts
|

Skin detection using fuzzy rule base system

Abstract: Skin detection is the process of finding skin pixels in a given color image. In this paper, we propose a novel fuzzy rule based system for robust and fast skin detection in color images. The proposed fuzzy system models the skin color distribution in HSV color space. Using the fuzzy model, skin likelihood of the pixel is calculated and if it exceeds a threshold then this pixels is considered as skin pixel. Also we proposed a multi layer perceptron neural network for skin classifier and compare its performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In [72] studied of the best fitting color space in skin detection as a case study for face detection by applying fuzzy logic concept in human skin modeling that can consider the light conditions and illumination. While in [73] used fuzzy rule model based system and skin likelihood, that can calculate pixel value. If it is exceeded threshold then it is considered as skin pixel.…”
Section: A: Pixel Basedmentioning
confidence: 99%
See 2 more Smart Citations
“…In [72] studied of the best fitting color space in skin detection as a case study for face detection by applying fuzzy logic concept in human skin modeling that can consider the light conditions and illumination. While in [73] used fuzzy rule model based system and skin likelihood, that can calculate pixel value. If it is exceeded threshold then it is considered as skin pixel.…”
Section: A: Pixel Basedmentioning
confidence: 99%
“…Adequate information about an image's real color of skin pixels can be obtained using the distribution of pixels of an image. Some authors [37], [42], [52], [73], [81], [111], [134], and [164] have noted that one of the challenges is that of varying conditions of illumination that can be adapted to the detection of human skin. Researcher also found that even after implementation of certain methods, the illumination still posed challenges in skin detection methods [12], [45], [87], [144], [165].…”
Section: ) Challenges Related To Illumination Variationmentioning
confidence: 99%
See 1 more Smart Citation